Pengaruh Model Pembelajaran Berbasis Masalah dengan Pendekatan Pemecahan Masalah terhadap Kemampuan Komunikasi Matematis Siswa - Adityawarman Hidayat (LPPM Universitas Pahlawan Tuanku Tambusai, 2015)
The cause of the low ability of students' communicationin mathematics learning in SMP Negeri Rumbio Jaya Kampar include learning method that is still centered on the teacher, one of the efforts is by using problem based learning model with problem solving approach. This research was conducted to improve the students’ communication mathematical ability. Type of the research is quasi-experimental (quasi-experimental). This study was conducted at grade VII SMP Negeri 1 Rumbio Jaya academic year 2013/2014. The researcher uses random sampling to take the sample. the test of communication ability of mathematical are used asthe instruments. Quantitative data were analyzed by using t-test for hypothesis 1and2, t’ test was used for hypothesis 3, and two-way Anova test for hypotheses 4. Based on the research that (1) students’ communication mathematical ability who are taught through problem based learning model with problem solving approach is better (2) there is no interaction between learning model with the students’ beginning knowledge in influencing students' communication mathematical ability.